Event-Based Time-Stamped Claim Logic - Ramos, Jaime; Rasga, João; Sernadas, Cristina; Viganò, Luca (Journal of logical and algebraic methods in programming, 2021)
The Event-Based Time-Stamped Claim Logic that we define in this paper allows one to reason about distributed time-stamped claims that can change through time by the occurrence of events. Such a logic is interesting for theoretical reasons, i.e., as a logic per se, but also because it can be applied in a number of different disciplines and application domains (e.g., history, crime forensics or cyber forensics) as it allows one to reason about a huge amount of pieces of evidence collected from different sources over time, where some of the pieces of evidence may be contradictory and some sources considered to be more trustworthy than others. We formalize the language and the semantics of the Event-Based Time-Stamped Claim Logic, provide a sound and complete Hilbert calculus, and consider some concrete examples. We also show that the validity problem for the logic is decidable by providing a tableau-like decision algorithm.